Ovarian Aging: Role of Pituitary-Ovarian Axis Hormones and ncRNAs in Regulating Ovarian Mitochondrial Activity - Colella, Marco; Cuomo, Danila; Peluso, Teresa; Falanga, Ilaria; Mallardo, Massimo; De Felice, Mario; Ambrosino, Concetta (Frontiers in Endocrinology, 2021)
The number of mitochondria in the oocyte along with their functions (e.g., energy production, scavenger activity) decline with age progression. Such multifaceted functions support several processes during oocyte maturation, ranging from energy supply to synthesis of the steroid hormones. Hence, it is hardly surprising that their impairment has been reported in both physiological and premature ovarian aging, wherein they are crucial players in the apoptotic processes that arise in aged ovaries. In any form, ovarian aging implies the progressive damage of the mitochondrial structure and activities as regards to ovarian germ and somatic cells. The imbalance in the circulating hormones and peptides (e.g., gonadotropins, estrogens, AMH, activins, and inhibins), active along the pituitary-ovarian axis, represents the biochemical sign of ovarian aging. Despite the progress accomplished in determining the key role of the mitochondria in preserving ovarian follicular number and health, their modulation by the hormonal signalling pathways involved in ovarian aging has been poorly and randomly explored. Yet characterizing this mechanism is pivotal to molecularly define the implication of mitochondrial dysfunction in physiological and premature ovarian aging, respectively. However, it is fairly difficult considering that the pathways associated with ovarian aging might affect mitochondria directly or by altering the activity, stability and localization of proteins controlling mitochondrial dynamics and functions, either unbalancing other cellular mediators, released by the mitochondria, such as non-coding RNAs (ncRNAs). We will focus on the mitochondrial ncRNAs (i.e., mitomiRs and mtlncRNAs), that retranslocate from the mitochondria to the nucleus, as active players in aging and describe their role in the nuclear-mitochondrial crosstalk and its modulation by the pituitary-ovarian hormone dependent pathways. In this review, we will illustrate mitochondria as targets of the signaling pathways dependent on hormones and peptides active along the pituitary/ovarian axis and as transducers, with a particular focus on the molecules retrieved in the mitochondria, mainly ncRNAs. Given their regulatory function in cellular activities we propose them as potential diagnostic markers and/or therapeutic targets.